Post-traumatic stress disorder and associated factors among inpatients at Eastern Command Referral Hospital in Dire Dawa, Eastern Ethiopia - Adugna, Desalegn; Yadeta, Tesfaye Assebe; Dereje, Jerman; Firdisa, Dawit; Demissie Darcho, Samuel; Kassa, Obsan; Kitessa, Monas; Gemeda, Asefa Tola (Frontiers in Psychiatry, 2024)
Background Post-traumatic stress disorder (PTSD) is characterized by heightened stress and anxiety after experiencing a traumatic event. While numerous studies have been conducted to investigate the magnitude and factors associated with PTSD, there is limited evidence available on specific study populations of military personnel. Objective The study aimed to determine the magnitude of post-traumatic stress disorder and associated factors among military personnel admitted to the Eastern Command Referral Hospital in Eastern Ethiopia from May 1 to 30, 2023. Methods and materials A cross-sectional study was carried out at an institution. Face-to-face interviews were conducted to collect data using the post-traumatic stress disorder military version checklist for the Diagnostic and Statistical Manual, Fifth Edition. Data were entered and analyzed using EpiData version 3.1 and STATA version 14. Descriptive statistics were employed to summarize the information. To investigate factors linked with outcome variables, bivariate and multivariate logistic regression analyses were conducted. The results were presented using odds ratios with 95% confidence intervals, with statistical significance given at a p-value of 0.05. Results This study found that approximately 23.6% (95% CI = 19.9–27.8) of admitted military members fulfilled the diagnostic criteria for PTSD. Participants’ history of mental illness [adjusted odds ratio (AOR) = 5.73, 95% CI = 2.66–12.31], family history of mental illness (AOR = 10.38, 95% CI = 5.36–20.10), current chewing of khat (AOR = 2.21, 95% CI = 1.13–4.32), physical trauma (AOR = 2.03, 95% CI = 1.00–4.13), moderate social support (AOR = 0.27, 95% CI = 0.1–4.53), strong social support (AOR = 0.09, 95% CI = 0.02–0.35), and severe depression (AOR = 2.06, 95% CI = 1.74–5.71) were factors significantly associated with post-traumatic stress disorder. Conclusions The magnitude of post-traumatic stress disorder is high among military personnel. Factors such as participants’ history of mental illness, family history of mental illness, depression, lack of social support, current use of khat, and physical trauma are significantly associated with PTSD. It is crucial to identify and intervene early in individuals with these risk factors to address PTSD effectively.